Dryopteris mengshanensis (dryopteridaceae) from china: a new species (Bangladesh Journal of Botany, 2024)
Dryopteris mengshanensis J. X. Li & X. J. Li, sp. nov. of Dryopteris Adans. belonging to Dryopteridaceae from Tashan mountain of Fei County, Linyi City, China is described and illustrated. It is closer to D. laoshanensis J. X. Li et S. T. Ma but differs for its height (60~78 cm), rhizome apex and stipe base densely covered with dark brown, margin brown, entire narrowly lanceolate scales, the upper middle of the stipe and the rachis densely covered with two types of small scales: 1) dark brown, entire narrowly lanceolate scales and 2) margin toothed, ovate-lanceolate scales. Leaves are ovate, bipinnate, pinnules oblong or rectangular circular, apex obtuse or flat, subentire margin. The lower middle of the rachis and stipe are castaneous, costae and rachiole have two kinds of small scales: 1) margin toothed lanceolate scales and 2) cystiform, apex caudate scales. Sori orbicular, larger, dorsal on both sides of the main vein below the middle of the pinnule, each in a line 4 to 5 pairs, located between the margin and midvein, less near the midvein. Spores perispore with massive ornamentation are very distinct.Bangladesh J. Bot. 53(3): 711-716, 2024 (September) Special